1996
DOI: 10.1111/j.1447-0756.1996.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

HER‐2/neu Gene Amplification in Cervical Cancer in Chinese Women of Hong Kong and China

Abstract: The results suggest that HER-2/neu amplification does exist in a subgroup of invasive cervical cancer and may play a role in cervical carcinogenesis. The role as independent prognostic factor has to be evaluated by further prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Our results are in disagreement with previous HER-2/neu studies on invasive cervical carcinomas that reported a higher rate of p185 c-erbB2 overexpression or HER-2/neu gene amplification (16)(17)(18)(19)(20)(21). This finding can be explained by differences in interpretation of p185 c-erbB2 immunolabeling and by different thresholds for the definition of p185 c-erbB2 overexpression.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Our results are in disagreement with previous HER-2/neu studies on invasive cervical carcinomas that reported a higher rate of p185 c-erbB2 overexpression or HER-2/neu gene amplification (16)(17)(18)(19)(20)(21). This finding can be explained by differences in interpretation of p185 c-erbB2 immunolabeling and by different thresholds for the definition of p185 c-erbB2 overexpression.…”
Section: Discussioncontrasting
confidence: 83%
“…Human papillomavirus (HPV) status was determined as previously described (24). Southern blot hybridization was the first-step procedure, using specific probes for HPV6, 11,16,18,31,33,35,39,42,45,52, and 58. A PCR with consensus primers in the L1 open reading frame was performed on cases negative by Southern blot hybridization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In endometrial adenocarcinoma the miRNA, miR-125b, inhibits the expression of HER2/neu and has been noted to be downregulated in HER2/neu-overexpressing endometrial adenocarcinoma samples [428]. Squamous cell carcinoma of the uterine cervix also expresses HER2/neu in 20-30% of the cases [10,377,415,[429][430][431][432][433][434][435][436][437] with approximately 50-75% of those cases demonstrating gene amplification [438][439][440][441][442]. Gene amplification is positively associated with the presence of HPV-6, a low -risk HPV serotype, in the cervical biopsies [443].…”
Section: Gynecologic Tumorsmentioning
confidence: 99%
“…According to previous studies, this protein is overexpressed in 12–70% of cervical cancers [7,13,14,15,16,17,18,19,20,21,22]. Overexpression of c-erbB-2 has been associated with more advanced disease stages, and a worse prognosis [13,14,15, 17,19,20,21,22]. However, these observations remain controversial and, hence, definitive conclusions cannot be drawn [7, 16, 18].…”
Section: Introductionmentioning
confidence: 99%